Complete Genome Sequence of Escherichia-Infecting Phage CEC_KAZ_2018, Isolated from Soil - Moldakhanov, Yergali S. (Microbiol Resour Announc, 2019)
Avian pathogenic Escherichia coli (APEC) bacteria are one of the main problems of the poultry industry. An effective way to combat colibacillosis is to use a phage preparation that lyses the bacteria. Here, we report the isolation of an E. coli-infecting phage, CEC_KAZ_2018, isolated from soil.